2022
DOI: 10.3389/fphys.2022.1010862
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage occlusion in ventricular assist device patients to decrease thromboembolic events: A computer simulation study

Abstract: Atrial fibrillation (AF) is a common comorbidity in left ventricular assist device (LVAD) patients and has been identified as a risk factor for thromboembolic stroke. Blood stagnation within the left atrial appendage (LAA) is considered a possible major source of thrombosis and clinical studies have shown reduced thromboembolic risk after LAA occlusion (LAAO). Therefore, this study aims to investigate the effect of LAAO on thrombosis-related parameters using patient-specific simulations. Left ventricular and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Several clinical investigations suggested that the risk of stroke could be reduced by utilizing hemodynamic data on the LA and mainly on the LAA [22,26,36,38,46,53,56]. Using a CFD approach, it is possible to access various biophysical indicators in a complex fluid dynamics system, such as velocity and pressure fields, cardiac blood flow rates, vorticity and turbulent kinetic energy, as well as specific metrics such as Wall Shear Stress (WSS), Time-Averaged Wall Shear Stress (TAWS), Oscillatory Shear Index (OSI), Residence Time (RT), and Endothelial Cell Activation Potential (ECAP) [3,[33][34][35][36]39,40,[42][43][44][45]47,50,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical investigations suggested that the risk of stroke could be reduced by utilizing hemodynamic data on the LA and mainly on the LAA [22,26,36,38,46,53,56]. Using a CFD approach, it is possible to access various biophysical indicators in a complex fluid dynamics system, such as velocity and pressure fields, cardiac blood flow rates, vorticity and turbulent kinetic energy, as well as specific metrics such as Wall Shear Stress (WSS), Time-Averaged Wall Shear Stress (TAWS), Oscillatory Shear Index (OSI), Residence Time (RT), and Endothelial Cell Activation Potential (ECAP) [3,[33][34][35][36]39,40,[42][43][44][45]47,50,53].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of closure devices is also analyzed in the literature [3,41,43,51]. A comparison between the results indicated that LAA closure significantly impacted blood flow velocity and paths.…”
Section: Discussionmentioning
confidence: 99%